PROBLEM BASED LEARNING DAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SD - Ariadi, Ahmad; Nahdia (Adi Widya: Jurnal Pendidikan Dasar, 2024)
Transformation of the world of education that is integrated with technology is very necessary in learning, a shift in people's lifestyles helps build a new culture. This has shifted many physical activities to online or digital. With this integration, the learning presented will be relevant to students' current circumstances and be able to provide improvements in learning outcomes. The problem solved in the research is the low level of student activity and also student learning outcomes during learning. This is due to the lack of student-centred learning activities and the lack of integration with technology as an attraction for student learning. This has an impact on students' learning patterns which become passive and the need for technological adaptability has not been met. To overcome and as an alternative to solving problems through the application of the Problem Based Learning model and the development of Augmented Reality as an integration of technology in learning. The aim of the research is to describe improving the quality of learning through student activities and analyzing learning outcomes. The research was carried out in four PTK meetings. The research object is 21 class IVB students. The research variables are activities and learning outcomes with the following results: student activity at the first meeting was 80.95%, the criteria for almost all students being very active, meeting 2 at 89.45%, the criteria for all students being active, meeting 3 at 100%, the criteria for all students being very active, and the fourth meeting was 100. The first meeting's student learning completion was 61.90% with the criteria that some students had completed, the second meeting had a score of 80.95% with the criteria that most students had completed, the third meeting was 90.48% with the criteria that almost all students had completed, and the fourth, 100%, in other words, all students achieve learning completeness.